Synthesis and characterization of some new organotellurium compounds based on quinoline - Al-Fregi, Adil Ali; Jaid, Haider Abdul-Sattar; Abdulsahib, Hassan Thamir (European Journal of Chemistry, 2017)
A new series of organotellurium compounds based on quinoline were prepared by the reaction of 8-(quinolyl)mercuric chloride (1) with tellurium tetrabromide in 1:1 and 1:2 mole ratio in dry dioxane to obtain 8-(quinolyl)tellurium tribromide (2) and bis[8-(quinolyl)]tellurium dibromide (3), respectively, in good yields. Reaction of compounds 2 and 3 by ethanolic hydrazine hydrate gave bis[8-(quinolyl)]ditelluride (4) and bis[8-(quinolyl)]telluride (5), respectively, in moderate yields. Furthermore, the ligand properties of bis[8-(quinolyl)] telluride (5) will be carried out with K2PtCl4, Na2PdCl4 and RhCl3.3H2O. All compounds were characterized by spectroscopic data and elemental analysis.